2019
DOI: 10.1002/hec.3939
|View full text |Cite
|
Sign up to set email alerts
|

Uncontrolled diabetes and health care utilisation: A bivariate latent Markov model approach

Abstract: Although uncontrolled diabetes (UD) or poor glycaemic control is a widespread condition with potentially life‐threatening consequences, there is sparse evidence of its effects on health care utilisation. We jointly model the propensities to consume health care and UD by employing an innovative bivariate latent Markov model that allows for dynamic unobserved heterogeneity, movements between latent states and the endogeneity of UD. We estimate the effects of UD on primary and secondary health care consumption us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…Compensated diabetes in 2014 does not affect the probability of experiencing a new complication in the following year. On the contrary, compensated patients are more likely to be hospitalised, which is in keeping with recent findings in Spain [Gil, Li Donni, Zucchelli, 2018]. Most controls included at GP level do not affect the observed outcomes.…”
Section: Resultssupporting
confidence: 89%
“…Compensated diabetes in 2014 does not affect the probability of experiencing a new complication in the following year. On the contrary, compensated patients are more likely to be hospitalised, which is in keeping with recent findings in Spain [Gil, Li Donni, Zucchelli, 2018]. Most controls included at GP level do not affect the observed outcomes.…”
Section: Resultssupporting
confidence: 89%
“…LMMs can be used as an extension of latent class analysis for longitudinal data and have been suggested in many studies for public health and medical research. In particular, an LMM is employed to study the performance of nursing homes [12] and their rankings [13], self‐reported health statuses based on longitudinal data [14], the effect of health status on material hardship [15], the effect of population aging on future health services costs [16], the diagnostics for trachoma elimination [17], the effects of uncontrolled diabetes on health care consumption [18], and model smoking transitions [19].…”
Section: Introductionmentioning
confidence: 99%